751. Decoding a Decade: Temporal Trends of MIC Distribution of Antifungals Against Cryptococcus species From a Reference Laboratory. (15th December 2022) - Ordaya, Eloy E; Abu Saleh, Omar M; Vergidis, Paschalis; Deml, Sharon; Wengenack, Nancy; Fida, Madiha
Abstract: Background: There are not established clinical breakpoints (CBP) for antifungals against Cryptococcus species; However, the analysis of their MICs using epidemiological cut-off values (ECVs) can help to distinguish wild-type (WT) isolates from non-WT strains that may harbor intrinsic or acquired resistance to antifungals. Herein, we analyze the MIC distribution of antifungals against Cryptococcus spp. isolated over the last decade at our reference laboratory. Methods: We conducted a retrospective evaluation of antifungals MICs for Cryptococcus neoformans and Cryptococcus gattii complex isolates from various sources that were processed at the Mayo Clinic Laboratory from November 18, 2011 to June 7, 2021. Antifungal susceptibility testing was performed by the Clinical & Laboratory Standards Institute (CLSI) standards (CLSI M59-ED3:2020). We used recommended ECVs to define if the isolates were WT or non-WT, and described the change in the percentage of WT isolates over time. Results: During the study period, C. neoformans was isolated from 632 samples collected from 533 patients. Sample sources included cultures from blood (n=301), cerebrospinal fluid (n=230), respiratory (n=71), and other sources (n=30). The overall percentage of WT isolates for amphotericin B (AMB), 5-flucytosine, and fluconazole were 77%, 98% and 91% respectively with no significant difference based on various sources (Table). We noticed an overall increase in MICs for AMB, with 100% WT isolates in 2011 compared to 79% in 2021. No such increase was seen for fluconazole or 5-Flucytosine (Figure). Irrespective of the source or the year of isolation, WT strains for itraconazole, voriconazole, and posaconazole were consistently > 93%. C. gattii was isolated from 16 samples, and 94% were WT strains for AMB and 100% for the other antifungals. CLSI, Clinical and Laboratory Standard Institute; CSF, cerebrospinal fluid; ECVs, epidemiologic cut-off values. AMB, amphotericin B; FLU, fluconazole; 5FC, 5-flucytosine. Conclusion: In the last decade, we have observed an overall increase in MICs of AMB for C. neoformans . The number of WT strains for other antifungals was high and not significantly changed during the study frame. Further studies are needed to identify the clinical implications of these findings. Disclosures: Paschalis Vergidis, MD, AbbVie: DSMB|Cidara: Grant/Research Support|Scynexis: Grant/Research Support.